Don't Open the Door - Brennan, Allison (Toronto, Ontario, Canada Mira, 2023)
Quitting her job and moving in the wake of the shocking murder of her son, Marshal Regan Merritt returns to Virginia to look into her former boss's death.
111685
Keywords: Merritt, Regan -- (Fictitious character) -- Fiction; United States -- Marshals Service -- Officials and employees -- Fiction; Children -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Children -- Death -- Fiction; Murder -- Fiction; Employees; Murder -- Investigation; Detective and mystery fiction; Fiction; Novels; Thrillers (Fiction)